Pengeluaran Pemerintah Daerah, Produktivitas Pertanian, dan Kemiskinan di Indonesia - Suwardi, Akbar (UI Scholars Hub, 2011)
This study aims to determine the relationship between local government spending, agricultural productivity, and poverty in Indonesia for the period of 2005-2008. Using econometric models of the panel and panel- simultaneous, this study find the evidence that local government spending on infrastructure and education significantly affect agricultural productivity and poverty. The study also found that the value of multiplier effect of local government spending on poverty, roads is the largest, followed by education (the literacy rate) and irrigation.